2003
DOI: 10.1046/j.1469-0691.2003.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subset numbers depend on the bacterial origin of sepsis

Abstract: Our results indicate that Gram-positive sepsis causes stronger suppression of peripheral blood lymphocyte subsets in comparison to sepsis due to Gram-negative pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 39 publications
3
53
1
2
Order By: Relevance
“…Therefore, a role for T lymphocytes in severe systemic bacterial infections has been described in several studies, and the findings of other investigations have supported the notion that T lymphocytes are involved in the pathogenesis of septic shock (Holub et al 2000;Holub et al 2003;Kabisch et al 1990;Lin et al 1993;Nishijima et al 1986). The NK compartment is characterized as CD3 -CD56 + cells that can be cytotoxic (CD16 + Bright) or produce high amount of cytokines such as IFNγ (CD16 + Dim) (Romagnani et al 2007).…”
Section: Role Of Peripheral Blood Lymphocytes In Septic Shock Outcomementioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, a role for T lymphocytes in severe systemic bacterial infections has been described in several studies, and the findings of other investigations have supported the notion that T lymphocytes are involved in the pathogenesis of septic shock (Holub et al 2000;Holub et al 2003;Kabisch et al 1990;Lin et al 1993;Nishijima et al 1986). The NK compartment is characterized as CD3 -CD56 + cells that can be cytotoxic (CD16 + Bright) or produce high amount of cytokines such as IFNγ (CD16 + Dim) (Romagnani et al 2007).…”
Section: Role Of Peripheral Blood Lymphocytes In Septic Shock Outcomementioning
confidence: 70%
“…The role of the lymphocytes in the septic shock it's not clear and it has been studied extensively in the last decades (Holub et al 2000;Holub et al 2003;Lin et al 1993;Menges et al 1999;Nishijima et al 1986). However, there are not many authors that have proposed to use lymphocytes as biomarkers for the outcome of these patients (Keane et al 1983;Monserrat et al 2009a).…”
Section: Role Of Peripheral Blood Lymphocytes In Septic Shock Outcomementioning
confidence: 99%
“…Nevertheless, the site of origin may be important, as suggested by a few papers revealing differences in the immune response during Gram + and Gram -sepsis. The study by Holub et al [4] showed that Gram + sepsis caused a higher decrease in CD4 + , CD8 + , NK cells and total T-lymphocytes than Gram -sepsis. The pattern of immune recovery in Gram + sepsis was different and slower than in Gram -infections [4].…”
Section: Discussionmentioning
confidence: 98%
“…The study by Holub et al [4] showed that Gram + sepsis caused a higher decrease in CD4 + , CD8 + , NK cells and total T-lymphocytes than Gram -sepsis. The pattern of immune recovery in Gram + sepsis was different and slower than in Gram -infections [4]. Gram positive sepsis is often related to higher mortality than Gram negative sepsis [12] and PDS is mostly of G + etiology, as in our observations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation